1366. Microbiology of Acute Hematogenous Osteomyelitis in Hospitalized Children. (31st December 2020) - Hu, Nina; Hamdy, Rana F; Martin, Benjamin
Abstract: Background: Acute hematogenous osteomyelitis affects 1 in 5, 000 children in the U.S. and Staphylococcus aureus is the most common bacterial cause. At our institution, clindamycin is used empirically for osteomyelitis, despite increasing clindamycin-resistance over the years. The objective of this study is to describe microbiologic results and antibiotic resistance patterns in children hospitalized with acute hematogenous osteomyelitis. Methods: This was a single-center retrospective cohort study of patients < 21 years of age with acute osteomyelitis hospitalized between 1/1/2010 and 5/31/2019 at Children's National Hospital. We excluded patients with recent orthopedic surgery, hardware infection, penetrating trauma, or with an underlying immunocompromising condition. We performed chart review to collect data on location of infection; blood, synovial fluid, or surgical site cultures; culture results, and susceptibilities. Results: Of the 162 encounters of acute osteomyelitis that met inclusion criteria, the average patient age was 8.3 years. Lower extremity infections were most common (105, 64.8%), followed by upper extremity (31, 19.1%), pelvis (14, 8.6%), spine (7, 4.3%), shoulder (4, 2.5%), rib (1, 0.6%) and mandible (1, 0.6%). Almost half of cases (73, 45%) had no positive cultures, and 89 cases (55%) had at least one positive culture from blood or local source (Figure 1). The most common pathogen was methicillin susceptible S. aureus (MSSA) followed by methicillin resistant S. aureus (MRSA) comprising 60 (67%) and 19 (20%) of culture-positive infections respectively. Other isolated pathogens included S. pyogenes (5, 5.6%) Salmonella species (2, 2.2%), S. pneumoniae (1, 1.1%), S. agalactiae (1, 1.1%), and Kingella kingae (1, 1.1%) (Figure 1). Among S. aureus infections, 69 (87%) were susceptible to clindamycin (85% among MSSA, 95% among MRSA). Categorized Blood and Wound Culture Results Conclusion: Almost half of all children with acute hematogenous osteomyelitis did not have any microbiologic data to guide antibiotic usage. S. aureus was the most common (87%) isolate, with more MSSA (74%) than MRSA (24%). Non- S. aureus isolates were more likely to grow from surgical specimen cultures than from blood cultures. Clindamycin resistance was more commonly seen in MSSA than in MRSA osteomyelitis. Disclosures: All Authors : No reported disclosures